THE EFFECT OF FIRM SIZE, PROFITABILITY AND PUBLIC OWNERSHIP STRUCTURE ON INCOME SMOOTHING AFTER THE IMPLICATION OF PSAK 50 AND 55 - Achmad Tezar Pahlevi Stefannandra; Negina Kencono Putri; Wita Ramadhanti; Rasyid Mei Mustofa (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2022)
PSAK 50 & 55 (revised) is important for the banking sector, as it aims to increase transparency, reducing disclosure that only benefit for banking managerial and narrow down the possibilities of fraud. Income smoothing is one form of fraud that management is often done to maximize the benefits for themselves, so that make any investor incorrect in making decisions for their investment. This study is a verification to test the truth of knowledge and previous research on banking companies listed on the IDX. This study takes the title: